Case 3690: Alabina Dall, 1902 (Gastropoda, Cerithioidea): proposed designation of the type species - Bouchet, P; Strong, EE (Bulletin of Zoological Nomenclature)
The purpose of this application, under Articles 65.2.2 and 70.2 of the Code, is to fix Alaba cerithidioides Dall, 1889 as type species of Alabina, as originally intended by Dall. Alabina Dall, 1902 (Gastropoda), is a replacement name for Elachista Dall & Simpson, 1901, non Elachista Treitschke, 1833 (Insecta). The name Elachista was introduced inadvertently a few weeks before its intended publication, with the consequence that its type species by monotypy is Bittium californicum Dall & Bartsch, 1901. Dall had intended it to be Alaba cerithidioides Dall, 1889, and he cited that species as type of Alabina in several publications. Bittium californicum Dall & Bartsch, 1901, and Alaba cerithidioides Dall, 1889, are not congeneric and not even confamilial.
Keywords: Nomenclature; taxonomy; ALABINIDAE; Alabina; Alaba cerithidioides; gastropods; western Atlantic